Paùlismo e interseccionismo pessoanos: interconexões sócio-históricas e plástico-estruturais - Jesus, Ronaldo Ribeiro de (2010)
This work aims at establishing a connection between the structural-plastic aspects of Paul-intersectionist poems by Fernando Pessoa and the sociohistorical context that generated them, with emphasis on the issue of fragmentation of the man of the early twentieth century. In order to do that, some of the theoretical frameworks used were: the conception of a fragmentary universe, by Theodor Erwin Rosenthal, the observations on the fusion technique of modern lyricism, according to Hugo Friedrich s notes, the myth of the androgyne described in The Banquet of Plato, as well as some of the major avant-garde manifestos of European Modernism. The poems selected to compose the corpus that constituted the basis for the development of the research are: Impressões do Crepúsculo (1913), which is the foundation of the paùlista program; Hora Absurda (1913), a composition of the militant phase of Modernism, Chuva Oblíqua (1914), considered the pinnacle of the sharpness and plasticity characteristic of the Intersectionism. At first, we focused on a brief reflection on the socio-historical context in which the European vanguardist movements have emerged, seeking to establish connections between them and the Paul-intersectionist experimentation; then we conducted a survey of some of the specific most significant reviews on Paulintersectionism; at last, we proceeded to the objective examination of the corpus. We concluded that although Paulism and Intersectionism have been disqualified by his creator, who once labeled them as a mere transitional period in his body of work, the texts of these two poetic systems developed stylistic features able to evoke the fragmentation of man of the early twentieth century. By proposing an innovative combination of textual fragments, Pessoa establishes a new expressive dimension, one of a simultaneist sort, able to expand our perception about the complex reality of the modern world